2022
DOI: 10.1186/s40510-022-00437-0
|View full text |Cite
|
Sign up to set email alerts
|

The impact of COVID-19 pandemic on total treatment time of fixed appliances

Abstract: Background Several aspects of the orthodontic routine seem to have been affected since the emergence of SARS-CoV-2. We aimed to evaluate the impact of the COVID-19 pandemic on the duration of fixed orthodontic treatment. Methods This retrospective study evaluated consecutive cases of patients undergoing fixed orthodontic treatment that completed treatment before (n = 37) or during (n = 26) the COVID-19 pandemic. The impact of the pandemic on treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…Because adolescents are motivated to undergo orthodontic treatment by the expected improvement in aesthetics, as well as self-confidence and self-esteem ( 13 ), they may consider the potentially worse treatment results and prolongation of orthodontic treatment as an additional disruption to their lives from the pandemic. Retrospective studies have shown that, although there were more absences and missed appointments for patients treated during the pandemic, the pandemic did not significantly affect total treatment time ( 14 , 15 ). However, certain elements of the peer assessment rating and objective grading system indices, such as maxillary alignment and buccolingual inclination, were worse in patients treated during the pandemic ( 15 ).…”
Section: Introductionmentioning
confidence: 99%
“…Because adolescents are motivated to undergo orthodontic treatment by the expected improvement in aesthetics, as well as self-confidence and self-esteem ( 13 ), they may consider the potentially worse treatment results and prolongation of orthodontic treatment as an additional disruption to their lives from the pandemic. Retrospective studies have shown that, although there were more absences and missed appointments for patients treated during the pandemic, the pandemic did not significantly affect total treatment time ( 14 , 15 ). However, certain elements of the peer assessment rating and objective grading system indices, such as maxillary alignment and buccolingual inclination, were worse in patients treated during the pandemic ( 15 ).…”
Section: Introductionmentioning
confidence: 99%